Modern Chinese Legal Reform : New Perspectives - Li, Xiaobing, 1954-; Fang, Qiang, 1968- (Book collections on Project MUSE., 2013)
China's rapid socioeconomic transformation around the turn of the twenty-first century has led to dramatic changes in its judicial system and legal practices. As China becomes more powerful on the world stage, the global community has dedicated more resources and attention to understanding the country's evolving democratization, and policymakers have identified the development of civil liberties and long-term legal reforms as crucial for the nation's acceptance as a global partner. This book is designed as a legal and political research tool to help English-speaking scholars interpret the many changes to China's legal system.